Experimental study on the influence of virtual tourism spatial situation on the tourists’ temperature comfort in the context of metaverse - Huang, Xiao-Ting; Wang, Jiahui; Wang, Zhihui; Wang, Linqiang; Cheng, Chenfei (Frontiers in Psychology, 2023)
The Metaverse is a new application of the internet and social form which integrates a myriad of new technologies. It can not only create a parallel space that is closely connected to the real world while highly independent, but also bring the immersive experience of virtual scenarios without delay. The virtual tourism space situations that integrate realistic visual, audio, and temperature sensations can restore the real tourism environment to the greatest extent, and improve tourists’ perception and satisfaction with the experience. The purpose of this experimental lab study is to examine the effects of the virtual tourism audio-visual conditions and environmental temperature on tourists’ thermal sensation and temperature comfort. VR equipment and microclimate simulation technology was applied in a 3 × 2 × 2 experimental design (n = 180), simulating the virtual tourism scenarios. Electrocardiogram devices were also employed to assess participants’ physiological indicators. Study results suggest that: (1) Virtual tourism spatial situations (environmental temperature and audio-visual conditions) significantly affect participants’ thermal sensation and part of the physiological indicators; (2) Virtual tourism spatial situations (environmental temperature and audio-visual conditions) significantly affect participants’ temperature comfort; and (3) Physiological responses (indicators) mediate the effect from tourism spatial situations to temperature comfort. The study mainly contributes to the literature about virtual tourism experience and spatial situations under the concept of the Metaverse, as well as provides theoretical and managerial implications for the development of “immersive” virtual tourism scenarios.